2019
DOI: 10.7602/jmis.2019.22.4.139
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Surgery for Rectal Cancer and Cost-Effectiveness

Abstract: Robotic surgery is considered as one of the advanced treatment modality of minimally invasive surgery for rectal cancer. Robotic rectal surgery has been performed for three decades and its application is gradually expanding along with technology development. It has several technical advantages which include magnified three-dimensional vision, better ergonomics, multiple articulated robotic instruments, and the opportunity to perform remote surgery. The technical benefits of robotic system can help to manipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 63 publications
1
8
0
3
Order By: Relevance
“…In our series, a shorter hospital stay was observed in the RG. These data are in accordance with the literature [ 25 ]. Larger studies have indeed also shown a shorter hospital stay with the laparoscopic approach [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our series, a shorter hospital stay was observed in the RG. These data are in accordance with the literature [ 25 ]. Larger studies have indeed also shown a shorter hospital stay with the laparoscopic approach [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Robotic platforms are also evolving. More agile platforms incorporating navigation systems will likely become available at lower costs [ 33 ]. However, no formal, standard accreditation for robotic surgery exists [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results are highly variable with some demonstrating greater cost-effectiveness of robotic surgeries overall and some finding that although the operative costs were higher, they may be mitigated or entirely outweighed when factoring in their associated reduced lengths of stays. [44][45][46][47][48][49] The development of ML algorithms currently being trialed in the health care landscape is often funded by individual researchers and their respective institutional or national research grants. 39 When evaluating the potential for a large-scale transformation of entire health care systems through the integration of AI/ML, due consideration must be offered towards determining which entity will bear this cost-the individual health system, the state, national research funding, and so forth.…”
Section: Financial Evaluations and Uncertaintiesmentioning
confidence: 99%